2022
DOI: 10.1371/journal.pone.0271468
|View full text |Cite
|
Sign up to set email alerts
|

Who is seeking help for psychological distress associated with the COVID-19 pandemic? Characterization of risk factors in 1269 participants accessing low-threshold psychological help

Abstract: Background The COVID-19 pandemic and accompanying restrictions are associated with substantial psychological distress. However, it is unclear how this increased strain translates into help-seeking behavior. Here, we aim to characterize those individuals who seek help for COVID-19 related psychological distress, and examine which factors are associated with their levels of distress in order to better characterize vulnerable groups. Methods We report data from 1269 help-seeking participants subscribing to a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Additionally, the lockdowns made it even more difficult for people to access services from mental health professionals (face-to-face) and some psychosocial services were also simply unavailable. Apart from that, studies also showed that seeking professional help during the period of was more common in women, younger people, people with higher education [ 61 ] and those with higher levels of anxiety or depression [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the lockdowns made it even more difficult for people to access services from mental health professionals (face-to-face) and some psychosocial services were also simply unavailable. Apart from that, studies also showed that seeking professional help during the period of was more common in women, younger people, people with higher education [ 61 ] and those with higher levels of anxiety or depression [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our study filled a knowledge gap by offering a wider perspective that considered macro and micro levels factors associated with generalized anxiety disorder among AYA. The literature on the global prevalence and burden of anxiety during COVID-19 pandemic showed a greater change in anxiety levels in younger ages compared to adults, and a stronger effect of the pandemic on adolescents’ mental health [ 31 , 32 , 33 ] reinforcing the importance of this study. Differences among countries in healthcare system structure, healthcare seeking behaviors stigmatization of mental problems and others are complex factors that need to be comprehensively studied following the suggested associations observed in the present study.…”
Section: Discussionmentioning
confidence: 71%
“…Patients completed a set of self-generated questions also used in a parallel survey from our group conducted in the general population [ 41 ] regarding health concerns and uncertainties, social isolation, financial worries, increased parenting, and work demands. In addition, we assessed depressive symptoms and changes in symptomatology of panic disorder, social anxiety disorder, and specific phobia.…”
Section: Methodsmentioning
confidence: 99%